Perencanaan Tenaga Kerja pada CV. Project Imaji Nusantara Bandung menggunakan Metode Workload Analysis - Nayla Salsabilah; Resya Dwi Marselina; Nada Zahra Salsabila; Nadila Siti Fauziah; Najwa Ainun Nabila (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Workforce planning plays a crucial role in ensuring the balance between workload and human resource capacity, particularly in creative industries characterized by project-based and flexible working systems. CV. Project Imaji Nusantara Bandung faces unstandardized task distribution dynamics, requiring a more measurable approach to identify workforce needs objectively. This study analyzes workforce planning, maps actual workload distribution, and determines optimal staffing requirements using the Workload Analysis (WLA) approach. A descriptive qualitative method with a case study design was applied. Data were collected through in-depth interviews, direct observation, and documentation of work activities, and validated using source and method triangulation. Data analysis employed Workload Analysis calculations by comparing total working hours and employees’ effective working time. The results indicate workload imbalance with a total of 360 working hours per month and 154 hours of effective working time, leading to an optimal requirement of 3 employees. The findings emphasize the importance of data-driven workforce planning to improve operational efficiency and employee well-being.